Persepsi Mahasiswa terhadap Implementasi Pembelajaran Berbasis Teknologi di Perguruan Tinggi - Kinanthi Rejeki, Suyekti (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
The advancement of technology has transformed higher education, driving the implementation of technology-based learning to enhance the efficiency and flexibility of teaching and learning processes. This study aims to analyze students’ perceptions of the implementation of technology-based learning in higher education through a literature review approach. The findings indicate that students generally perceive technology-based learning positively due to its ability to facilitate information access, improve digital skills, and support flexible learning schedules. However, challenges such as limited infrastructure in certain areas, lecturers' technological competence, and potential distractions from digital devices were identified. Factors influencing students’ perceptions include technology accessibility, personal experience with technology, and the quality of learning interactions. This study highlights the importance of developing infrastructure, providing training for lecturers, and adopting innovative approaches to overcome barriers in technology-based learning. These recommendations aim to improve the effectiveness of higher education and foster an inclusive learning environment in the digital era.